2018
DOI: 10.1253/circj.cj-18-0031
|View full text |Cite
|
Sign up to set email alerts
|

Association of N-Terminal Pro B-Type Natriuretic Peptide With Blood Pressure and Pulse Pressure in Elderly People ― A Cross-Sectional Population Study ―

Abstract: The results suggest that NT-proBNP concentrations may be a marker of not only ventricular dysfunction, but also arterial stiffness in the elderly population without CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The latter increases with age independently of mean BP or any other determinant factors. Sasaki et al have shown that NT‐proBNP concentrations may be a marker of not only ventricular dysfunction, but also arterial stiffness in the older population without CVD disease. NT‐proBNP was positively associated with SBP, whereas a U‐shaped association was found between DBP and NT‐proBNP.…”
Section: Pathophysiology and Complications Of Hypertension In Older Amentioning
confidence: 99%
“…The latter increases with age independently of mean BP or any other determinant factors. Sasaki et al have shown that NT‐proBNP concentrations may be a marker of not only ventricular dysfunction, but also arterial stiffness in the older population without CVD disease. NT‐proBNP was positively associated with SBP, whereas a U‐shaped association was found between DBP and NT‐proBNP.…”
Section: Pathophysiology and Complications Of Hypertension In Older Amentioning
confidence: 99%
“…An increase in NT-proBNP was associated with increasing pressures while the most robust decrease in NT-proBNP across visits corresponded with significant reduction in SBP between these visits. Prior studies have found that SBP is positively associated with NT-proBNP and mediates association with CVD events . Although the observational nature of our study prevents determination of causality, previous clinical trials have established the importance of blood pressure control in the reduction of HF risk .…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, we assessed the association between CCA parameters and the serum NT-proBNP level by adjusting for confounding factors, including the age, sex (31), BMI (32), hemoglobin concentration (33), and indices of blood pressure (34). The sex-related differences in the serum NT-proBNP level are well known (31), and consistent with previous reports, we confirmed the significantly higher serum NT-proBNP level in women than in men in this study (data not shown).…”
Section: Discussionmentioning
confidence: 99%